Evaluation of a commercial enzyme‐linked immunosorbent assay for detection of antibodies against the H5 subtype of Influenza A virus in waterfowl. Issue 6 (22nd December 2012) - Lebarbenchon, Camille; Pantin‐Jackwood, Mary; Kistler, Whitney M.; Page Luttrell, M.; Spackman, Erica; Stallknecht, David E.; Brown, Justin D.
<x xml:space="preserve">Abstract</x> The ID Screen Influenza H5 Antibody Competition enzyme‐linked immunosorbent assay was tested for the detection of antibodies to the H5 subtype of influenza A (IA) virus in waterfowl. Assays were conducted with sera obtained from Mallards (Anas platyrhynchos) and Pekin Ducks (Anas platyrhynchos domestica), experimentally infected with eight low pathogenic (LP) and nine highly pathogenic (HP) H5N1 IA viral strains. Three incubation periods (1, 4 and 18 hours) and two dilutions (1:2 and 1:5) were tested. All serum samples from LP H5‐infected birds tested positive; however, improved detection rates were observed for viruses belonging to the HP H5N1 clade 2.2.1 as compared with those belonging to clade 2.1.3.